EFFECTS OF NEEM (AZADIRACHTA INDICA L.) SEED CAKE ON THE GROWTH AND YIELD OF OKRA (ABELMOSCHUS ESCULENTUS (L.) MOENCH) - Ehiokhilen Kevin Eifediyi; Kehinde Olayemi Mohammed; Samson Uduzei Remison (Poljoprivreda, 2015)
Soils of the southern Guinea savannah are generally inherently infertile owing to low vegetation cover, soil erosion and low organic matter content due to constant bush fire. Consequently, farmers move close to streams and rivers in the dry season where okra is cultivated by irrigation. Field experiments were conducted at the Teaching and Research Farm of the University of Ilorin, Ilorin Nigeria during the 2012 and 2013 cropping seasons to evaluate the effects of neem seed cake on the performance of okra. The neem seed cake was incorporated into the soil one week before sowing of the okra seeds at the rate of 0, 1, 2, 3 and 4 t/ha. The experiment was laid out as a randomized complete block design replicated thrice. Data were collected on growth parameters (plant height, number of leaves and number of branches) and yield parameters (fruit length and girth, number of fruits per plant, fruit weight per plant and fruit weight per hectare). The result indicated that applying neem seed cake significantly affected the growth and yield parameters that were evaluated. Applying neem seed cake, however gave the highest yield at 3t/ha. Percentage mean for the two years combined was 75.81% over the control.